ANALISIS PENILAIAN KINERJA KEUANGAN DENGAN MENGGUNAKAN RASIO PROFITABILITAS (Studi Kasus Pada PT. Express Trasindo Tbk Tahun 2018-2020) - rachmawati, siti; Sulistiyawati, Sulistiyawati; Shofiana, Adib Aulia; Citradewi, Adelina (Jurnal Akuntansi Syariah (JAkSya), 2022)
This study aims to find out the reasons why return on assets (ROA) tends to increase and return on equity (ROE) in 2019 tends to decrease. This study uses descriptive methods and data collection techniques used in this study are qualitative data and quantitative data in the form of numbers and data. The qualitative data used is a general description of the company PT Express Transindo Utama Tbk. As quantitative data in this study, the financial statements of PT Express Transindo Utama Tbk for 2018-2020. The result of this research is that the return on assets (ROA) tends to increase, this is because the companyÔÇÖs profit increases even though the assets owned by the company decrease. The companyÔÇÖs profit increased along with the decrease in the companyÔÇÖs operating costs and the decline in return on equity (ROE) in 2019 indicating the companyÔÇÖs inability to generate return on equity..